Docência universitária em disciplinas a distância em cursos presenciais: um estudo sobre as práticas didático-pedagógicas - Parreira Júnior, Walteno Martins (2012)
The theme of this research is the university teaching practice, in teacher graduating courses which adopt the semipresential modality, analyzing specifically professors didacticpedagogical performance in distance (or semipresential) disciplines in presential courses. The main objective is to reflect on the official documents of the Education Ministry that support semipresential courses, analyzing its efficacy. Thus, it seeks to understand, by questioning professors who teach in these courses, their own didactic-pedagogical practice, with emphasis on the teaching-learning process, the instructional material used, the teacher-student interaction and the evaluating process of their students. Using the qualitative and quantitative approach, it was applied a survey instrument, consisting of three parts: in the first, the respondent is qualified; in the second, consisting of statements, the professor evaluates the importance of the programmed contents to his own teaching activity; and the third one consists of an open question. In the second part of the survey instrument, the professors declarations were assessed by the five points Likert scale. The research informants are professors in two courses of a university education institution in Ituiutaba, in Minas Gerais State. It was observed that the official documents on distance education, in Brazil, contributed to the expansion and organization of this teaching modality, since the approval of the LDB to its regulations; which comprises a set of rules that allow qualified institutions to offer courses, and, to the regulating bodies, it represents the instruments for measuring the quality of these courses. Furthermore, the research has identified that the respondent professors are using the information and communication technologies (ICTs) in the teaching-learning process not only for interacting with their students, organizing present and develop the contents of their disciplines, but also to develop the evaluating activities. It is hoped that further studies on the offering of semipresential graduating courses are made to know more about this teaching modality, which has not completed ten years and requires the development of an appropriate didactic-pedagogical practice.